Comparative analysis of differentially acetylated proteins between Antarctic white‐blooded Chionodraco hamatus and red‐blooded Trematomus bernacchii - Ruonan Jia; Wanying Zhai; Shaojun Huang; Boyu Chen; Ruiqin Hu; Shouwen Jiang; Qianghua Xu (Journal of Fish Biology, 2026)
Protein acetylation is a critical post‐translational modification that regulates a wide range of cellular functions. The Antarctic icefish, which lack haemoglobin and functional red blood cells, serves as a unique model to explore the impact of acetylation on haematopoiesis and cold‐adaptive epigenetic mechanisms. Despite its relevance, the specific acetylation mechanisms in Antarctic fish remain poorly understood. In this study, we utilized a comprehensive methodology combining tandem mass tag labelling, high‐performance liquid chromatography fractionation, Kac antibody affinity enrichment and liquid chromatography–tandem mass spectrometry to quantify and compare acetylation patterns in the haematopoietic tissues of the head kidney between a white‐blooded icefish Chionodraco hamatus and a red‐blooded species Trematomus bernacchii . A total of 167 acetylation sites on lysine residues were identified across 77 differentially acetylated proteins, including 10 proteins with upregulated acetylation and eight proteins with downregulated acetylation between the two species. Kyoto Encyclopedia of Genes and Genomes pathway analysis of these proteins indicated significant enrichment in the ‘Cell proliferation and cell cycle’, ‘P53 signaling pathway’, and ‘FoxO signaling pathway’ for the upregulated acetylated proteins in the icefish head kidney, while ‘Systemic lupus erythematosus pathways’ and ‘Gene regulation pathways’ were found in the downregulated proteins. Furthermore, a marked reduction in acetylation of the histone H2B type 1‐M‐like (H2B) protein was observed in the icefish head kidney, potentially reflecting the species' extremely low red blood cell production. This study represents the first detailed exploration of protein acetylation in Antarctic fish and provides valuable insights into the epigenetic adaptations of marine vertebrates to cold environments.